CHARACTERISTICS OF BRAND FORMATION IN UZBEKISTAN MANUFACTURING ENTERPRISES IN ACCORDANCE WITH NATIONAL TRADITIONS (Marketing Journal, 2025)
This article analyzes the process of forming brands that adhere to national traditions in manufacturing enterprises in Uzbekistan. It examines the economic factors, marketing strategies, and consumer behavior that influence the creation and competitiveness of a national brand in the international market. According to the research findings, the demand for national products in Uzbekistan continues to grow, and stable growth rates are observed in the manufacturing sector. Consumersʼ trust in local products is strengthening, and both ecological sustainability and innovative technologies play a significant role in production processes. Furthermore, state support for manufacturing enterprises, an increase in investment volumes, and the expansion of export potential are considered key factors in the development of national brands. The study also provides a detailed review of the role of di gital marketing, e -commerce, and international trade fairs in the process of forming a national brand. Based on statistical data, scientific research results, and survey analysis, the article presents promising directions for the development of national brands and offers strategic recommendations. It examines advanced practices in brand management, marketin g technologies, and innovative production systems, and formulates conclusions aimed at enhancing the competitiveness of Uzbek enterprises in the international market.
Keywords: national brand; manufacturing enterprises; marketing strategy; consumer behavior; export potential; ecological sustainability; innovative technologies; digital marketing; e -commerce; economic development; international market; brand management